Survei pengimejan elektrik dan georadar dalam kajian tanah runtuh Taman Hill View,Ampang Selangor - Umar Hamzah,; Nurul Fairuz Diyana Bahrudin,; Mohd Azmi Ismail,; Amry Amin Abbas, (Universiti Kebangsaan Malaysia, 2009)
Electrical resistivity and Ground Penetrating Radar (GPR) surveys were carried out at Taman Hill View, Ampang, Selangor landslide area. This landslide site was a part of three similar landslides which occurred at Bukit Antarabangsa, Hulu Klang, Selangor. The landslide had occurred along the road to Bukit Antarabangsa and Athenaeum Tower. The objectives of these studies were to characterise the sliding material and to determine the depth of bedrock below the sliding surface using the electrical resistivity imaging technique as well as to recognise the fractured or weak zone using the GPR technique. The spacing between electrodes used in the survey was 2 to 2.5 m and the survey lines were chosen close to the borehole locations. With a total of 41 electrodes and spacing between each electrode of 2 to 2.5 m, the maximum current electrode spacing in this survey would be between 80-100 m resulting in the deepest subsurface depth investigated approximately at 20 to 25 m. A 100 MHz electromagnetic wave was used in the Ground Penetration Radar survey. The resistivity imaging result showed the weathered granite profile with resistivity value ranging from 2 to 7000 Ωm. The patterns also show that this area had a lot of fractured or weak zones up to a depth of 4 to 5 m based on the occurrence of low resistivities zones in between the high resistivities. These highly fractured and faulted zones also appeared in the GPR sections as shown by the presence of shifted reflectors and layer discontinuity.